Pengaruh Intensitas Cahaya Berbeda Terhadap Kepadatan dan Kandungan Karotenoid Dunaliella salina - Febriani, Rivi; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Perikanan dan Kelautan, 2020)
Microalgae has an important role in the world of fisheries, because the availability of microalgae is needed as a natural feed in the hatchery business of fish and shrimp. One type of microalgae that is potential to be developed as a natural feed is Dunaliella salina. Factors that influence affect the density and carotenoids of D. salina is the intensity of light because it has an important role in the process of photosynthesis. This study aims to get the best light intensity in increasing the density and content of D. salina carotenoids. This research was conducted on 12-21 May 2019. Located in the Natural Feed Laboratory, Center for Brackish Aquaculture Fisheries (BBPBAP) Jepara. The research method used was a Completely Randomized Design with 4 treatments giving different light intensities namely P1 (2,500 lux), P2 (3,500 lux), P3 (4,500 lux) and P4 (5,500 lux) with 3 replications. Growth was observed for 10 days by calculating daily density and carotenoid content on the 6th day. The results showed that different light intensities affected the density and content of D. salina carotenoids. The highest density and carotenoid content was found in the light intensity of 5,500 lux with a density of 637.87 x 10 4 cells /ml and the carotenoid content of 1.45 µg /ml.